2007
DOI: 10.1007/s11433-007-0051-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphologies of solid-liquid interface and surface steps during rapid growth of BaB2O4 single crystals

Abstract: The evolution of solid-liquid interface during BBO single crystal growth was studied by the differential interference microscopy. And the step morphology on (0001) surface of the as-grown crystal was observed by the atomic force microscopy as well. It was found that the transition from a flat solid-liquid interface to a skeletal shape will occur in case of rapid growth. However, AFM images of surface steps revealed morphology differences correlated with crystallographic directions. The steps advancing along < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…It hints that the present glass matrix can in some sense be treated as a high-temperature solution since layer-like growth usually occurs in solution system [11]. As for the problem how BBO step propagates in high-temperature solution, much thorough work has been done in our previous papers [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…It hints that the present glass matrix can in some sense be treated as a high-temperature solution since layer-like growth usually occurs in solution system [11]. As for the problem how BBO step propagates in high-temperature solution, much thorough work has been done in our previous papers [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous works [5,6] have shown that, for oxide melt morphological instability will occur and skeletal or dendritic shape will be obtained during rapid growth. In this work, using an in situ observation system, we distinguished diffusive and convective effects on crystal morphological stability in case of high cooling rate.…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of multifunctional crystal, crystal growth of ADP was extensively studied. In recent years, much progress was achieved on crystal growth [2−5], especially at the aspect of increasing the crystal growth rate and improving crystal quality [6,7]. As for ADP crystal, the research works mainly focused on ADP rapid growth technique, the effect of doping on the properties of ADP crystals and KADP (NH 4 H 2 PO 4 -KH 2 PO 4 ) crystal growth [8−10].…”
mentioning
confidence: 99%